Framing and Group Polarisation in Hate Speeches in Nigeria - Ugwu, Justus Chidi; Nnnamani, Obiageli C. (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2023)
Since the Nigerian Civil War in 1970, there has been a mutual suspicion among its three major ethnic groups, Hausa (in the North), Igbo (East) and Yoruba (West). This is not only manifest in their socio-political life but has also generated strife and hate speech, typified by context-sensitive strategies. This paper highlights the key group-motivated strategies of framing and polarisation utilized in the hate speeches raised by different groups in the Nigerian political discourse. The 2017 Kaduna declaration by a northern union (Arewa Youths), threatening to evict the Igbo living in the northern region, and response texts from other unions to the declaration constitute the data. These were subjected to content analysis with insights from van Dijk’s Ideological Representation and Halliday and Matthiessen’s Transitivity Theory. The findings reveal a self-preservationist frame, which is polarised in the Self/Other pattern.